PENYULUHAN TENTANG PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) TERHADAP PENINGKATAN KESADARAN ANAK DI SDN 23 PANJI JORONG KOTO MALINTANG NAGARI KOTO TANGAH KECAMATAN AGAM - Sari, Yuli Permata; Diyastari, Afriza; Yulfian, Revo Gibran; Shidiq, Ikbal; Musa, Syahrul; Hidayaturrahman, Taufik; Ramadhan, Ahmad; Sari, Endah Fita; Andiny, Shinta Putri; Febriyanti, Dinda Mesra; Az-zahra, Hamida; Fitri, Mona Annis; Ferlani, Shinta; Hanifa, Siti Millata (MAJU : Indonesian Journal of Community Empowerment, 2025)
Health education is an effective method in increasing public understanding and awareness regarding Clean and Healthy Living Behavior (PHBS). This outreach aims to evaluate the effectiveness of PHBS outreach activities in increasing community knowledge and attitudes regarding healthy lifestyles. The research method used was quantitative with a pre-test and post-test design on 69  respondents selected by purposive sampling. Extension is carried out through lecture methods, interactive discussions, and PHBS practice simulations. The results of the study showed a significant increase in the level of knowledge (p < 0.05) and positive changes in attitudes towards implementing PHBS, especially in hand washing habits, clean water consumption and waste management. These results indicate that counseling is an effective strategy in building awareness and changing healthy behavior. Therefore, PHBS counseling needs to be carried out regularly and continuously with the support of health workers and the local government